1,4,6-Trisubstituted imidazo[4,5-c]pyridines as inhibitors of Bruton's tyrosine kinase - Krajčovičová, Soňa; Jorda, Radek; Vanda, David; Soural, Miroslav; Kryštof, Vladimír (European journal of medicinal chemistry, 2021)
Herein, we report an efficient synthetic approach towards trisubstituted imidazo [4,5-c]pyridines designed as inhibitors of Bruton's tyrosine kinase (BTK). Two alternative synthetic routes for the simple preparation of desired compounds with variable substitutions at the N1, C4, C6 positions were introduced with readily available building blocks. Further, the developed synthetic approach was feasible for isomeric compounds bearing imidazo [4,5-b]pyridine scaffolds. In contrast to expectations based on previous studies, the imidazo [4,5-c]pyridine inhibitor exhibited a significantly higher activity against BTK compared to its imidazo [4,5-b]pyridine isomer. An inherent SAR study in the series of imidazo [4,5-c]pyridine compounds revealed a remarkably high tolerance of C6 substitutions for both hydrophobic and hydrophilic substituents. Preliminary cellular experiments indicated selective BTK targeting in Burkitt lymphoma and mantle cell lymphoma cell lines. The inhibitors could thus serve as starting points for further development, eventually leading to BTK inhibitors that could be used after ibrutinib failure.
Keywords: signální transdukce; Signal Transduction; proteinkinasa BTK; nehodgkinský lymfom; Humans; Inhibitor; inhibitory proteinkinas; simulace molekulového dockingu; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Protein kinase; Molecular Docking Simulation; lidé; Pyridines; Lymphoma, Non-Hodgkin; Bruton’s tyrosine kinase; Protein Kinase Inhibitors; pyridiny; imidazo[4,5-c]pyridine; Agammaglobulinaemia Tyrosine Kinase